Performance of the Indian Banking Industry:A Comparison of Public and Private Sector Banks - Shukla, Shalini (Indian Journal of Finance, 2016)
The paper sought to analyze the performance of the banking industry in India on the basis of established financial parameters. By using the purposive sampling technique, 46 scheduled commercial banks were studied and the business standard banking annual database was explored to collect the relevant information. Both public and private sector banks were included in the sample and analyzed on the basis of four parameters (size, growth, profitability, and soundness) segregated into 11 financial performance indicators. The findings highlighted that public and private sector banks were not very much different in terms of size and growth parameters. However, significant differences were found in terms of profitability and soundness of business, indicating robust growth prospects for private sector banks. The study represented a pioneering and seminal attempt to provide a number of implications for policy makers, budding researchers, and professionals.